Grx2 Regulates Skeletal Muscle Mitochondrial Structure and Autophagy - Liaghati, Ava; Pileggi, Chantal A.; Parmar, Gaganvir; Patten, David A.; Hadzimustafic, Nina; Cuillerier, Alexanne; Menzies, Keir J.; Burelle, Yan; Harper, Mary-Ellen (Frontiers in Physiology, 2021)
Glutathione is an important antioxidant that regulates cellular redox status and is disordered in many disease states. Glutaredoxin 2 (Grx2) is a glutathione-dependent oxidoreductase that plays a pivotal role in redox control by catalyzing reversible protein deglutathionylation. As oxidized glutathione (GSSG) can stimulate mitochondrial fusion, we hypothesized that Grx2 may contribute to the maintenance of mitochondrial dynamics and ultrastructure. Here, we demonstrate that Grx2 deletion results in decreased GSH:GSSG, with a marked increase of GSSG in primary muscle cells isolated from C57BL/6 Grx2-/- mice. The altered glutathione redox was accompanied by increased mitochondrial length, consistent with a more fused mitochondrial reticulum. Electron microscopy of Grx2-/- skeletal muscle fibres revealed decreased mitochondrial surface area, profoundly disordered ultrastructure and the appearance of multi-lamellar structures. Immunoblot analysis revealed that autophagic flux was augmented in Grx2-/- muscle as demonstrated by an increase in the ratio of LC3II/I expression. These molecular changes resulted in impaired complex I respiration and complex IV activity, smaller diameter of tibialis anterior muscle, and decreased body weight in Grx2 deficient mice. Together, these are the first results to show that Grx2 regulates skeletal muscle mitochondrial structure, and autophagy.